An investigation into the cognitive and neuropsychological sequelae of minor head injury in children – a prospective pilot study. (26th December 2010) - Kerr, Jacques
Abstract : Objectives: Although the majority of head-injured children are Glasgow Coma Scale (GCS) 15 and do not require admission or further investigations there is evidence that some children with a minor head injury (MHI) will go on to experience significant morphological and functional brain deficits. In view of the lack of controlled studies into the sequelae of MHI in children we carried out a pilot study that examined the neuropsychological performance in children who had sustained an MHI. Methods: Children aged 6–12 years who presented to the Emergency Department of the Royal Hospital for Sick Children in Edinburgh with a MHI (GCS 15) were recruited to the study. Neuropsychological assessment was performed using the Cambridge Neuropsychological Test Automated Battery (CANTAB); a computerised battery of tests, which measures motor skills, visual attention, spatial memory, working memory and non-verbal memory span. CANTAB also assesses executive function, which is the highest level of cognitive function that manages planning and allows flexible thought and action. Results: 15 head-injured children were recruited over the study period (eleven boys and four girls). A 2 (subject groups) × 3 (time points) repeated measures Analysis of variance was used on the number of problems solved using the minimum number of computer moves at each time point, which showed a significant interaction (p=0.003). Bonferroni posthoc comparisons demonstrated that in week 1 the head-injured group were significantly lower in performance compared to normative data (p=0.03), but significantly increased in performance between week 1 and 12 months (p=0.0001). The difference in the head-injured group performance between week 1 and week 6 approached significance (p=0.05). Conclusion: The MHI group show a significantly poorer performance with regards to problem-solving in a minimum number of moves, which may indicate impulsive tendencies and insufficient planning ability. Children with a MHI may therefore be at risk of developing problems with high-level cognitive function postinjury.